x + 2y = 1

x = 1 - 2y -----------------------------1

2x + 3y = 4 --------------------------2

Putting the value of x in 2

2 ( 1 - 2y ) + 3y = 4

2 - 4y + 3y = 4

-y = 2

y = -2

For x , putting the value of y in 1

x = 1 - 2y

x = 1 - 2 ( -2 )

x = 5

2.

3m - n = 5

3m = 5 + n

m =

3

2m+5n = 7 --------------------2

Putting the value of m in 2

2 (

10 + 2n + 15n = 21

17n = 11

n = 11/17

For m ptting the value of n

Now do it yourself.

x + 2y = 1

x = 1 - 2y -----------------------------1

2x + 3y = 4 --------------------------2

Substitute the value of x in 2 equation

2 ( 1 - 2y ) + 3y = 4

2 - 4y + 3y = 4

-y = 2

y = -2

Substitute the value of y in 1 equation

x = 1 - 2y

x = 1 - 2 ( -2 )

x = 5

2 solution

3m - n = 5

3m = 5 + n

m =

3

2m+5n = 7 --------------------2

Putting the value of m in 2

2 (

10 + 2n + 15n = 21

17n = 11

n = 11/17

Substitue the value of n in 11/17 in euation 1

3m-11/17=5

51m-11/17=5

51m-11=85

51m=85+11=96

m=96/51

x + 2y = 1

x = 1 - 2y -----------------------------1

2x + 3y = 4 --------------------------2

Putting the value of x in 2

2 ( 1 - 2y ) + 3y = 4

2 - 4y + 3y = 4

-y = 2

y = -2

For x , putting the value of y in 1

x = 1 - 2y

x = 1 - 2 ( -2 )

x = 5

2.

3m - n = 5

3m = 5 + n

m = 5 + n --------------------1

3

2m+5n = 7 --------------------2